DESAIN ETL PENENTUAN PENEMPATAN KERJA PRAKTEK MAHASISWA (studi kasus : Fakultas Ilmu Komputer UPN : Veteran" Jakarta) - Naufal Nashrullah, - (2018)
The importance of information about students who previously took courses to provide useful information for universities to see the students from the results that can be obtained from practical work and provide advice to students who make the Data Warehouse job. In designing ETL design based on the case used by writer using life cycle database system (SDLC) with waterfall metedology with systematic and gradual sequence. Therefore the results obtained are information to make decisions in various activities that have been done by previous students to help new students who want to do practical work to find out the company information that is appropriate to use the workplace practice. which will then be an extraction process that will run with a unique base table ETL process and an ETL algorithm that will run automatically when the transaction process is not executed simultaneously when the daily database backup transactions